Alterations of c‐di‐GMP turnover proteins modulate semi‐constitutive rdar biofilm formation in commensal and uropathogenic Escherichia coli. Issue 5 (15th September 2017) - Cimdins, Annika; Simm, Roger; Li, Fengyang; Lüthje, Petra; Thorell, Kaisa; Sjöling, Åsa; Brauner, Annelie; Römling, Ute
Abstract: Agar plate‐based biofilm of enterobacteria like Escherichia coli is characterized by expression of the extracellular matrix components amyloid curli and cellulose exopolysaccharide, which can be visually enhanced upon addition of the dye Congo Red, resulting in a red, dry, and rough (rdar) colony morphology. Expression of the rdar morphotype depends on the transcriptional regulator CsgD and occurs predominantly at ambient temperature in model strains. In contrast, commensal and pathogenic isolates frequently express the csgD ‐dependent rdar morphotype semi‐constitutively, also at human host body temperature. To unravel the molecular basis of temperature‐independent rdar morphotype expression, biofilm components and c‐di‐GMP turnover proteins of seven commensal and uropathogenic E. coli isolates were analyzed. A diversity within the c‐di‐GMP signaling network was uncovered which suggests alteration of activity of the trigger phosphodiesterase YciR to contribute to (up)regulation of csgD expression and consequently semi‐constitutive rdar morphotype development. Abstract : This study is the first to address the molecular mechanisms behind semi‐constitutive rdar biofilm expression of both commensal and uropathogenic E. coli isolates. We employed genome sequencing to directly link genome alterations to distinct, semi‐constitutive, rdar biofilm phenotypes. This work significantly contributes to our understanding of the variability and development of the cyclic di‐GMP network in E. coli and highlights the impact of single amino acid mutations for protein functionality.